2016
DOI: 10.1021/acscatal.6b00798
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of Water Oxidation Catalyzed by a Dinuclear Cobalt Polypyridine Complex: Identification of CoOx as a Real Heterogeneous Catalyst

Abstract: Recently, a dinuclear cobalt complex, [(TPA)Co III (µ-OH)(µ-O 2 )Co III (TPA)] (ClO 4 ) 3 (1, TPA = tris(2-pyridylmethyl)amine), has been reported as a homogeneous catalyst for electrochemical and photochemical water oxidation (Wang et al. Angew. Chem. Int. Ed. 2014, 53, 14499.). During the re-investigation of the reported water oxidation catalyst (WOC) of 1, several characterizations such as EDTA and bipyridine titrations, electrochemistry, SEM, EDX, ICP-AES, TEM, XPS and UV-vis spectroscopy have revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
102
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(107 citation statements)
references
References 53 publications
5
102
0
Order By: Relevance
“…Cobalt‐based cluster as molecular water oxidation catalysts have been studied widely because of the characterization of cheapness and easily procurable to different oxidation state of cobalt . In 2010, one molecular cobalt catalyst, [Co 4 (H 2 O) 2 (PW 9 O 34 ) 2 ] 10− , which contains two polyhedral [PW 9 O 34 ] units symmetrically attached a planar Co 4 O 16 core, was reported by Hill's group .…”
Section: Homometallic 3d Metal Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobalt‐based cluster as molecular water oxidation catalysts have been studied widely because of the characterization of cheapness and easily procurable to different oxidation state of cobalt . In 2010, one molecular cobalt catalyst, [Co 4 (H 2 O) 2 (PW 9 O 34 ) 2 ] 10− , which contains two polyhedral [PW 9 O 34 ] units symmetrically attached a planar Co 4 O 16 core, was reported by Hill's group .…”
Section: Homometallic 3d Metal Clustersmentioning
confidence: 99%
“…Cobalt-based cluster as molecular water oxidation catalysts have been studied widely because of the characterization of cheapness and easily procurable to different oxidation state of cobalt. [36][37][38][39][40][41][42] Hill's group. [43][44] It was a soluble molecular catalyst based on noble-metal-free metals.…”
Section: Co-based Clustersmentioning
confidence: 99%
“…They usually get deactivated when immobilized on electrode surfaces and they suffer from instability due to hydrolytic behavior and decomposition into metal-oxides upon oxidation of the organic ligands. 3 However, from an engineering perspective, solid-state electroanodes are desired due to the simplicity of assembly for potential devices. Therefore, it is imperative to understand the influence of the anchoring functionality on the performance of the immobilized catalysts to learn how to anchor and stabilize functional molecular catalysts on electrode surfaces.…”
mentioning
confidence: 99%
“…As a result, no catalytic current was observed compared to the background with a freshly polished GC electrode ( Figure S9), further demonstrating the electrocatalysis of 1 is homogeneous. [48] Additionally, adding one equivalent of bipyridine in the CV solution of 1.0 mmol•L 1 1 did not cause the current decrease, demonstrating the catalytic water oxidation is due to the complex rather than the free copper ions ( Figure S10). [48] The SEM images ( Figure S11) and EDX measurement ( Figure S12) on the GC plate after CPE revealed that only trace of copper species was found on the electrode surface.…”
Section: Resultsmentioning
confidence: 97%
“…[48] Additionally, adding one equivalent of bipyridine in the CV solution of 1.0 mmol•L 1 1 did not cause the current decrease, demonstrating the catalytic water oxidation is due to the complex rather than the free copper ions ( Figure S10). [48] The SEM images ( Figure S11) and EDX measurement ( Figure S12) on the GC plate after CPE revealed that only trace of copper species was found on the electrode surface. The Cu residue on the GC electrode might originate from trace amount of 1 absorbed on the surface of working electrode or inactive copper phosphate.…”
Section: Resultsmentioning
confidence: 97%